2021
DOI: 10.1111/ajad.13219
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of drug‐related dreams in opioid use disorder

Abstract: Background and Objectives Drug‐related dreams are commonly reported by individuals in treatment for substance use disorders, which may be distressing. Existing evidence suggests that dream recollection may be influenced by clinically relevant phenomena, such as opioid use and withdrawal, general sleep disturbance, affective symptoms, and chronic pain. However, very few studies have explored drug‐related dreams among individuals who screened positive for opioid use disorder (OUD). Methods Adults recruited from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…As with opioid-mediated antinociception, the relationship between opioids, sleep/wake disturbances and sex is still being unraveled (Tripathi et al, 2020;Huhn and Finan, 2021). Some evidence suggests women are more likely to experience opioid-induced sleep disturbances (OISD) (Finan et al, 2020;Ellis et al, 2022). Importantly, OISD are emerging as a promising therapeutic target for opioid use disorder (Huhn and Finan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As with opioid-mediated antinociception, the relationship between opioids, sleep/wake disturbances and sex is still being unraveled (Tripathi et al, 2020;Huhn and Finan, 2021). Some evidence suggests women are more likely to experience opioid-induced sleep disturbances (OISD) (Finan et al, 2020;Ellis et al, 2022). Importantly, OISD are emerging as a promising therapeutic target for opioid use disorder (Huhn and Finan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of patients with opioid use disorder (OUD) reported that recalling drug-related dreams from the past week may report more sleep disturbances, including poorer sleep quality, and more severe insomnia symptoms. Substantial increases in drug cravings following dreams have been associated with greater anxiety symptoms [50]. Sleep duration and disorders can affect anxiety symptoms, and similarly, increased anxiety level can negatively affect sleep; for example, excessive worry about insomnia may exacerbate sleep disturbances [51].…”
Section: Discussionmentioning
confidence: 99%
“…To be eligible, they needed to be over 18 years old and currently in treatment or recovery for OUD. For additional information, see Ellis et al (2022a). The study was formally submitted to and acknowledged by the Johns Hopkins School of Medicine Institutional Review Board as exempt from human subjects research due to the deidentified nature of data collection.…”
Section: Participantsmentioning
confidence: 99%
“…Insomnia is a common co-occurring condition in OUD, as well as a known side effect of opioid withdrawal (Huhn et al, 2022;Ellis et al, 2022a). In order to sleep, some individuals resort to using opioids to prevent this symptom of withdrawal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation